Societal Perceptions Toward Income Inequality During the Process of Economic Development: Evidence from International Panel Data - WANNAPHONG DURONGKAVEROJ (Asian Development Review, 2025)
While economic inequality has gained prominence in the contemporary development debate, the reasons why the degree of tolerance for inequality varies among countries remain an unresolved issue. This knowledge gap has resulted in excessive policy emphasis on inequality in some countries where absolute poverty is rampant. The purpose of this paper is to address the issue through multi-economy panel data analysis using an analytical framework that draws on Hirschman’s (1973) assertion on the “changing tolerance for income inequality in the course of economic development.” Tolerance for inequality is measured by societal perceptions of inequality using data from the World Values Survey. The results suggest that the willingness to accept inequality remains positive at the early stage of economic development, when inequality is increasing, and then tends to turn negative. The results are robust to alternative specifications and measures of income inequality.